A TRANSITIONS STUDIES PERSPECTIVE ON THE SOCIAL ECONOMY; EXPLORING INSTITUTIONALIZATION AND CAPTURE IN FLEMISH 'INSERTION' PRACTICES. (26th April 2017) - PEL, Bonno; BAULER, Tom
ABSTRACT: Current persistent challenges of sustainable and equitable development call for systemic technical and social innovations. The ´insertion´ practices of work integration social enterprises (WISEs) can be considered examples of such innovation efforts. The underlying rationales and institutional frameworks have been elaborated extensively in social economy scholarship. However, as WISEs are frequently reported to fall victim to pressures towards isomorphism or 'capture' by incumbent institutional structures, transitions theory seems worthwhile to invoke in order to develop a dynamic understanding of these processes. As illustrated through case study data on the Flemish social economy, it is highlighted how ´insertion´ displays longitudinal dynamics of institutional capture that are similar to those observed in sustainability transitions more generally. This empirical analysis helps to identify the scope for fruitful paradigmatic interplay between transitions studies and social economy scholarship.